The haunting - Lasky, Kathryn (Lasky, Kathryn. Secret of Glendunny, 2022)
Deep in the wilds of Scotland, there is a secret colony of beavers. After being vilified and nearly hunted to extinction, the beavers retreated to this safe haven, and no beaver has been seen in Scotland or England for over five hundred years. But when the young beaver, Dunwattle, is sighted, he puts the entire colony at risk. Destined to be destroyed, Dunwattle's best friend Locksley is determined to save him. Along the way, they discover a secret involving a mysterious young girl who is almost one thousand years old.